Long-Term Follow-Up of Restorations of Equine Cheek Teeth Infundibula (2006–2017) - Pearce, Christopher J.; Brooks, Nicky (Frontiers in Veterinary Science, 2022)
Background: Caries of the infundibula of equine cheek teeth can lead to significant dental disease including increased attritional wear, pulpar and apical disease, secondary sinusitis, and dental fracture. Restorations of cavities of equine cheek teeth infundibula have been performed since 1889. Recent advances in dental materials, instrumentation, and techniques have facilitated the use of dental restoration techniques by equine veterinary practitioners. No studies to date have demonstrated the safety or efficacy of restorations of equine cheek teeth infundibula. Objectives: To assess the long-term results of restorations of equine cheek teeth affected by infundibular caries, to report on the safety of the procedure, and to give guidelines for future restorative therapies. Study Design: Retrospective analysis of results of clinical and oroscopic examination of horses that underwent infundibular restoration procedures between 2006 and 2017. Methods: A total of 223 infundibula in 185 maxillary cheek teeth in 92 horses were restored using a variety of dental materials including glass ionomer cement, flowable and compactible resin composites. The time between restoration and re-examination was recorded along with findings of clinical signs in the interim, restorative material loss, and any further pathological changes of the teeth including caries progression, fracture, or apical disease. Follow-up examinations were performed over two study periods 2006–2012 and in 2017. Results: Over the full study period, 99% of treated horses available for follow-up examinations had no adverse clinical signs or developed any abnormalities of restored teeth observable on oroscopic examination. Of horses re-examined, 83% of restorations were shown to have minimal or no loss of the restoration material, with occlusal surface wear visibly comparable to other adjacent maxillary teeth. Statistical analysis showed success of the procedure was related to the restorative material used, the restoration technique, and the caries grade present at the time of restoration (grade 3 is more successful than grade 2). Main Limitations: There are no case controls in this study and therefore it is not clear if restoration of equine infundibula is a consistently beneficial procedure, or at which grade of caries progression restorations should be performed for optimum benefit. The procedures were not re-examined at consistent regular times creating some difficulties in standardizing results. Re-examinations of treated horses did not consistently include radiography or computed tomography and therefore some apical changes may have occurred in treated teeth without visual oroscopic or external clinical signs. Conclusion: Restoration of equine infundibula using materials developed for human dentistry including flowable resin composites is a safe and long-lasting procedure and appears to prevent the development of further pathological changes including apical infection and dental fracture.